To solve the equation 7x = 15 + 6 using substitution, we need to substitute the expression on the right-hand side of the equation with a single variable.
We can simplify the right-hand side by adding 15 and 6 to get 21.
Now, the equation becomes:
7x = 21.
To solve for x, we divide both sides of the equation by 7:
(7x)/7 = 21/7.
Simplifying, we get:
x = 3.
Therefore, the solution to the equation 7x = 15 + 6 is x = 3.
solve the equation 7x = 15 + 6 using substitution.
x = ?
3 answers
are you sure?
Apologies for the mistake. Let's solve the equation correctly using substitution:
Given equation: 7x = 15 + 6.
To use substitution, we substitute the expression on the right-hand side (15 + 6) with its simplified value (21). So the equation becomes:
7x = 21.
Now, we divide both sides of the equation by 7 to solve for x:
(7x)/7 = 21/7.
Simplifying, we get:
x = 3.
Therefore, the solution to the equation 7x = 15 + 6 using substitution is x = 3.
Given equation: 7x = 15 + 6.
To use substitution, we substitute the expression on the right-hand side (15 + 6) with its simplified value (21). So the equation becomes:
7x = 21.
Now, we divide both sides of the equation by 7 to solve for x:
(7x)/7 = 21/7.
Simplifying, we get:
x = 3.
Therefore, the solution to the equation 7x = 15 + 6 using substitution is x = 3.